(untitled) (Bangladesh Journal of Medical Science, 2022)
Background:MNS glycophorin variants such as glycoprotein (GP.) Mur, GP.Hop, GP.Bun, GP.HF, GP.Hut, and GP.Vw are known to carry multiple antigens, including Mia (MNS7). In East and Southeast Asians, an antibody to Mia is not only commonly found, but also clinically significant. Purpose and Methods: In this study, deoxyribonucleic acid (DNA) samples from 47 patients suspected of having anti-Mia by serological screening were genotyped for GP.Mur, GP.Hop, GP.Bun, GP.HF, GP.Hut, and GP.Vw variants using polymerase chain reaction (PCR) assay. Results: All patients were found to be negative for the presence of Mia-positive glycophorin variants. Conclusions: The presence of anti-Mia cannot be excluded in patients studied, as genotyping shows that Mia-positive MNS glycophorin variants are not present. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 432-437